Женская гордость: роман / Мишель Рид - Рид Мишель (Панорама романов о любви, 1998)
Экземпляры: ф.20 (2004) / Инвентарный номер: 48280 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Р 49 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44